Ayurvedic Management of Vicharchika Through Panchkarma - Khushbhu Sharma; Atul Pawar (AYUSHDHARA, 2024)
Ayurveda holds crucial and traditional space in the world of medicine. In spite of various challenges, Ayurveda continued to flourish its roots and spreading its fragrance all around the world through ages. Our Vedas holds various introduction and explanation about diseases along with their treatment whose complete curable treatment not available in today’s developed period. One such disease is Vicharchika Acharya’s in Brihatryi included Vicharchika in Kshudra kustha. According to Ayurvedic diagnostic criteria Pidika, Kandu, Srava, Twak syavata seen. In Ayurveda, this disease mainly treated with shaman and Shodhan chikitsa In contemporary medicine world, this disease correlated with eczema and no satisfactory result with curable symptom not established till now with increased chances of relapse.